Development of non-financial reporting system as a business efficiency improving tool - Zh. M. Korzovatykh (Вестник университета)
The problem of increasing informativeness about all the components of the activities of economic entities is the basis for emergence of non-financial reporting system. It discloses non-financial information about the environmental status of an organization, its social responsibility, and sustainable development for the continuity of activities and careful attitude to nature. The activities of economic actors affect all spheres of social life and the environment as well, so the issue of non-financial reporting is relevant. The article studies state regulation of the system and identifies the need for area management and control. In order to effectively assess the contribution of an economic entity to the economy and the environment of a country, uniform standards for the composition and content of information disclosed in non-financial reporting and mandatory reflection parameters depending on the industry affiliation of companies, strategic orientation, and focus on the future are necessary to be used. Content-analysis of scientific publications on the system and general scientific methods of knowledge (systematic approach, logical generalization, and hypotheses) have been used as the methods of the research. The purpose of the study is to determine the main directions of harmonization of financial and non-financial reporting allowing to collect, evaluate, and analyze all the characteristics of an organization in the aggregate and increase the reliability of information about the economic entity as a whole.